PENGEMBANGAN WISATA MERAPI GARDEN BERBASIS PERAN MASYARAKAT LOKAL DI SELO BOYOLALI - Donna Setiawati; Fera Tri Wulandari (EKOBIS, 2022)
Tourism villages need to be developed so that they can provide benefits to the surrounding community. The development process requires the participation of local communities starting from the planning, implementation and monitoring stages. Even though in reality conditions in the community, community participation or participation is often neglected. This study aims to examine the involvement of local communities in the development of the tourist village of Merapi Garden. Data collection techniques using unstructured interviews and documentation. The technique of checking the validity of the data uses triangulation and data analysis techniques in this research interactive model, namely by reducing data, presenting data, and verifying or drawing a conclusion. The results of this study are that there is an active role in providing input and involvement of the local community in the development of the Merapi Garden tourism village, which is carried out from the planning stage to its implementation.